Evaluating Computation and Data Placements in Edge Infrastructures through a Common Simulator - Silva, Anderson Andrei Da; Mommessin, Clément; Neyron, Pierre; Trystram, Denis; Bauskar, Adwait; Lebre, Adrien; Kempen, Alexandre Van; Ngoko, Yanik; Ricordel, Yoann (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
Scheduling computational jobs with data-sets dependencies is an important challenge of edge computing infrastructures. Although several strategies have been proposed, they have been evaluated through ad-hoc simulator extensions that are, when available, usually not maintained. This is a critical problem because it prevents researchers to –easily– perform fair comparisons between different proposals. In this paper, we propose to address this limitation by presenting a simulation engine dedicated to the evaluation and comparison of scheduling and data movement policies for edge computing use-cases. Built upon the Batsim/SimGrid toolkit, our tool includes an injector that allows the simulator to replay a series of events captured in real infrastructures. It also includes a controller that supervises storage entities and data transfers during the simulation, and a plug-in system that allows researchers to add new models to cope with the diversity of edge computing devices. We demonstrate the relevance of such a simulation toolkit by studying two scheduling strategies with four data movement policies on top of a simulated version of the Qarnot Computing platform, a production edge infrastructure based on smart heaters. We chose this use-case as it illustrates the heterogeneity as well as the uncertainties of edge infrastructures. Our ultimate goal is to gather industry and academics around a common simulator so that efforts made by one group can be factorised by others.